Human Parechovirus Infections Associated with Seizures and Rash in Infants and Toddlers. Issue 10 (October 2015) - Karsch, Katharina; Obermeier, Patrick; Seeber, Lea; Chen, Xi; Tief, Franziska; Mühlhans, Susann; Hoppe, Christian; Conrad, Tim; Böttcher, Sindy; Diedrich, Sabine; Rath, Barbara
Abstract : Background: Systematic investigations assessing the clinical impact of human parechovirus (HPeV) disease are sparse. Noninvasive stool samples may be useful for targeted hospital-based surveillance. Methods: In the context of a quality management program, all hospitalized children fulfilling predefined case criteria for central nervous system (CNS) infection/inflammation underwent standardized neurologic examinations. Stool samples were collected for HPeV and enterovirus (EV) polymerase chain reaction and molecular typing at the National Reference Center. Results: From October 2010 to December 2012, stool samples of 284 patients with suspected CNS infection/inflammation were tested yielding 12 (4.2%) HPeV+ samples and 43 (15.1%) EV+ samples. HPeV-positive samples included HPeV-1, HPeV-3 and HPeV-6. No additional pathogens were identified in routine care. HPeV-positive patients were significantly younger ( P < 0.001) and more likely to present with seizures ( P = 0.001) and rash ( P < 0.0001) when compared with HPeV-negative patients. Conclusions: In hospitalized children younger than 4 years presenting with suspected CNS infection/inflammation, seizures and/or rash, HPeV should be considered in the differential diagnosis. Large-scale public health surveillance may be indicated. Abstract : Supplemental Digital Content is available in the text.